2017
DOI: 10.4309/jgi.2016.34.9
|View full text |Cite
|
Sign up to set email alerts
|

Gambling and Video Game Playing Among Youth

Abstract: Gambling and video game playing represent two leisure activities in which adolescents and young adults participate. There are psychological and behavioural parallels between slot machine gambling and video arcade game playing. Because both activities have similar negative effects associated with excessive play (e.g., poor academic performance, moodiness, loss of interest in activities previously enjoyed, interpersonal conflict) there is concern that children and adolescents who are attracted to video games, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 207 publications
(375 reference statements)
1
17
0
1
Order By: Relevance
“…Most studies observed whether young people had ever participated in gambling or had gambled within the previous 12 months, and reported the prevalence of problem gambling, which was typically reported as low or moderate risk of problem gambling, or problem gambling. Lifetime participation in gambling rates ranged between 42.1% [10] and 89.9% [20], with the majority of studies that examined gambling participation reporting that around a third or more of adolescents or young adults confirmed that they had gambled at least once in their lifetime [10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Gambling participation rates during the past 12 months ranged between 18.6% [38] to 85% [23].…”
Section: Gambling Participation and Problem Gamblingmentioning
confidence: 99%
“…Most studies observed whether young people had ever participated in gambling or had gambled within the previous 12 months, and reported the prevalence of problem gambling, which was typically reported as low or moderate risk of problem gambling, or problem gambling. Lifetime participation in gambling rates ranged between 42.1% [10] and 89.9% [20], with the majority of studies that examined gambling participation reporting that around a third or more of adolescents or young adults confirmed that they had gambled at least once in their lifetime [10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Gambling participation rates during the past 12 months ranged between 18.6% [38] to 85% [23].…”
Section: Gambling Participation and Problem Gamblingmentioning
confidence: 99%
“…For example, Molde et al [75] identified video gaming as a potential gateway behaviour to problem gambling. A study by McBride et al [76] found adolescents who played video games were significantly more likely to have gambled online for money. Forrest et al [77] found that the link between video gaming and gambling frequency was related to age, with those who did gamble being slightly older on average than those who did not.…”
Section: Video Gaming and Gamblingmentioning
confidence: 99%
“…One study has also revealed a strengthening, albeit of a relatively small magnitude, of the link between the amount of money spent on loot boxes and problem gambling when players command the ability to cash out loot box prizes, the option to pay to win, and when players experience near misses . Links have also been found between the amount of money spent on loot boxes and the amount of time spent playing video games (Li et al, 2019;McBride & Derevensky, 2016), and between the spending of money on microtransactions and the probability of players migrating to traditional online gambling (Kim et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%